What would happen to the trees and lianas if apes disappeared?. Issue 3 (27th February 2015) - Beaune, David
Abstract: Apes, like many frugivorous animals, are crucial allies for the reproduction of several fruiting tree species. Almost all apes, however, including bonobos Pan paniscus, are threatened with extinction. How will this affect tree conservation? How can plants that are adapted to seed dispersal by apes reproduce without their dispersal vectors? At LuiKotale, in an evergreen tropical forest of the Democratic Republic of Congo, the recruitment of 22 plant species in the absence of seed dispersal was investigated under the parental canopy, where a proportion of seeds fall without horizontal dissemination. Most bonobo-dispersed plant species (95% of 19 species) were unable to self-recruit under the canopy. As 40% of the tree species (65% of trees) at LuiKotale are dispersed by bonobos there is a risk of ecosystem decay and simplification (reduced biodiversity) if Pan paniscus disappears from its natural range. The extinction of other apes from their forests could have similar consequences. The conservation of tree species, therefore, must encompass conservation of pollinators, seed dispersal vectors and other species that provide ecological services to the trees and other fruiting plants.